Perancangan Interior Pusat Informasi Tanaman Obat di Surabaya - Christie Valerina Soewono (Intra, 2015)
Medical Plants Information Center in Surabaya is a space that gives the learning facility, information, as well as recreation place for Surabaya tourists. The Indonesian medical plants are known for its excellence in alternative medication. Unfortunately, Indonesian people rarely knows the way to plant these medical plants and there has not yet been any interesting indoor facility that can facilitate the needs of information and education for the people.The applied design method is The Disney Method which is a paralel thinking method where designer must analyze the problem, come up with an idea, evaluate the idea, and critique the chosen design. This design uses the Sense of Herbs concept and using the theme of mengkudu plant which uses its senses as an information sharing media. This information center is an indoor garden that is supported by the athmosphere of natural modern. The facilities includes information center, library, staff rooms, laboratory, and plants storeroom.